History of Bangladesh 1704-1971, volume three, social and cultural history - Islam, Sirajul, 1939-; Miah, Sajahan; Asiatic Society of Bangladesh (Dhaka, Bangladesh : Asiatic Society of Bangladesh : Distributing agent, Academic Publishers, 2007)
Contributed articles.
v. 1. Political history -- v. 2. Economic history -- v. 3. Social and cultural history.
Includes bibliographical references with each chapter.
Paragon Enterprises(18420)
Hye Trade Inernational, Book Finder International
Keywords: Bangladesh -- History; Bengal (India) -- History